Public Policies for Agricultural Diversification: Implications for Gender Equity - Valencia, Vivian; Wittman, Hannah; Jones, Andrew D.; Blesh, Jennifer (Frontiers in Sustainable Food Systems, 2021)
Although gender equity is recognized as central to sustainable development, women still face significant constraints in accessing and controlling productive resources important for agricultural livelihoods. Identifying mechanisms by which policies and interventions in agriculture may enhance women’s empowerment—a critical aspect of gender equity—is of paramount importance for sustainable development. We investigated how targeted public food procurement, a promising policy instrument to support farm diversification, influences women’s empowerment. We also discuss how targeted public food procurement may bridge across Sustainable Development Goals (SDGs), particularly SDG 1 “No Poverty”, SDG 2 “Zero Hunger”, and SDG 5 “Gender Equality,” to support transformation of food systems towards sustainability. Specifically, we assessed Brazil’s flagship public food procurement program, the National School Feeding Program, in southern Brazil. We compared farmers (n=75) who do and do not participate in the National School Feeding Program and conducted household surveys on farm characteristics and practices, women’s empowerment (as related to participation in farm decision-making and control over income), and women’s participation in social movements. We found that women were more empowered in households participating in the National School Feeding Program, and that this empowerment was associated with diversified farming systems. When women were more empowered and, therefore, jointly participated in farm management with male farmers, we found that agrobiodiversity and use of agroecological practices were at their highest. Finally, we show that women’s participation in social movements related to agroecology was associated with both higher empowerment and household participation in the National School Feeding Program. Targeted public food procurement is a promising policy instrument to support multiple SDGs by linking cross-sectoral efforts to increase food production (SDG 2), provide economic opportunities for small-scale farmers (SDG 1), and create an economic space that women in agriculture can more easily access (SDG 5).